2017
DOI: 10.3389/fnint.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

Visual Distractors Disrupt Audiovisual Integration Regardless of Stimulus Complexity

Abstract: The intricate relationship between multisensory integration and attention has been extensively researched in the multisensory field; however, the necessity of attention for the binding of multisensory stimuli remains contested. In the current study, we investigated whether diverting attention from well-known multisensory tasks would disrupt integration and whether the complexity of the stimulus and task modulated this interaction. A secondary objective of this study was to investigate individual differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 103 publications
2
40
1
Order By: Relevance
“…To that end, we compare different families of probability distributions (e.g., the Gaussian, Normal, Lognormal, Exponential and Gamma) and choose the best fit in an MLE sense. Owing to our prior works using the ABIDE sets (Torres and Denisova, 2016 ; Torres et al, 2017 ) we determined that the Gamma had the best fit in an MLE sense. As such, we settled on the continuous Gamma family of probability distributions (Ross, 1983 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To that end, we compare different families of probability distributions (e.g., the Gaussian, Normal, Lognormal, Exponential and Gamma) and choose the best fit in an MLE sense. Owing to our prior works using the ABIDE sets (Torres and Denisova, 2016 ; Torres et al, 2017 ) we determined that the Gamma had the best fit in an MLE sense. As such, we settled on the continuous Gamma family of probability distributions (Ross, 1983 ).…”
Section: Methodsmentioning
confidence: 99%
“…The variable degree of skewness we have previously found in the empirical distributions of linear and angular speed peaks derived from these ABIDE data (Torres et al, 2017 ) sets motivated us to further explore the possibility that different random processes may underlie the time series data collected under different SR. As such, here we try to elucidate the quality of the noise inherently present in the variability of the speed-dependent raw data comprising all the original frames of the studies of ABIDE (i.e., without scrubbing the images).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Findings of a recent study (Matusz et al, 2015 ) suggested that conclusions about the distribution of attentional resources across the sensory modalities for adults do not necessarily generalize to children. In addition, we want to note that another effective means to circumvent limitations in one sensory modality is by providing redundant information via several sensory modalities, thereby taking advantage of the behavioral benefits of multisensory integration (i.e., faster reaction times and a higher accuracy) (Meredith and Stein, 1983 ; Ernst and Banks, 2002 ; Helbig and Ernst, 2008 ; Stein and Stanford, 2008 ; Gibney et al, 2017 ). The process of multisensory integration has been argued to be independent of top-down influences (Matusz and Eimer, 2011 ; De Meo et al, 2015 ; ten Oever et al, 2016 ) and be robust against additional attentional demands (Wahn and König, 2015a , b ) for low-level stimuli (for more general reviews on the topic, see van Atteveldt et al, 2014 ; Chen and Spence, 2016 ; Macaluso et al, 2016 ; Tang et al, 2016 ), making it highly suitable to circumvent limitations within one sensory modality.…”
Section: Circumventing Limitations Of Visuospatial Attentionmentioning
confidence: 99%